LMS Mediated Blended Learning in English for Academic Purpose: Pharmacy Students’ View - Rahman, Faisal; Azmi, Aulia (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
This study aims to identify pharmacy students’ perception on the implementation of Learning Management System (LMS) mediated blended learning in English for Academic Purpose (EAP) course. The scope of this study is in several factors, such as the use of LMS in blended learning, and the effectiveness of blended learning in EAP context to develop students’ motivation, communication skill, vocabulary, critical thinking and social interaction according to the students’ perception. This research utilizes a quantitative approach employing an analytical survey with an exploratory component using Likert scale questionnaire to collect the data. The population of this research is 115 students of pharmacy taking EAP course. The sample is 35 students selected using simple random sampling technique. This study reveals that blended learning is perceived positively by students in this EAP course, particularly for developing core skills and understanding the subject matter. Additionally, blended learning is also considered interesting and enjoyable. However, there is room for improvement in fostering critical thinking and social interaction. This result recommends educators to implement LMS mediated blended learning in English Language teaching and learning with several improvement, especially in the way to improve students’ critical thinking and social interaction.